2022
DOI: 10.1021/acs.orglett.2c01310
|View full text |Cite
|
Sign up to set email alerts
|

Tetrazolo[1,5-a]pyridine-Containing π-Conjugated Systems: Synthesis, Properties, and Semiconducting Characteristics

Abstract: The incorporation of an electron-accepting unit into π-conjugated systems is an important approach to modulate the physical properties of such molecules. To investigate the potential of tetrazolo­[1,5-a]­pyridine as an electron-accepting unit, a series of diarylated tetrazolo­[1,5-a]­pyridine derivatives was synthesized by treating the corresponding diarylated pyridine N-oxide with diphenylphosphoryl azide. Thermogravimetric analyses of these molecules indicated that they possessed good thermal stability. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…[6][7][8] Pyridine nitrogen oxides are a class of common organic compounds containing pyridine, which are extensively utilized in pharmaceutical synthesis and other elds due to their diverse synthesis pathways, superior biological activity, ease of synthesis, and excellent chelating ability. [9][10][11][12][13][14][15][16][17][18][19][20][21] Literature reports have demonstrated that complexes of pyridine nitrogen oxides and transition metals exhibit considerable anticancer and antibacterial activities, 22,23 making them valuable in biomedicine and as antimicrobial materials.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Pyridine nitrogen oxides are a class of common organic compounds containing pyridine, which are extensively utilized in pharmaceutical synthesis and other elds due to their diverse synthesis pathways, superior biological activity, ease of synthesis, and excellent chelating ability. [9][10][11][12][13][14][15][16][17][18][19][20][21] Literature reports have demonstrated that complexes of pyridine nitrogen oxides and transition metals exhibit considerable anticancer and antibacterial activities, 22,23 making them valuable in biomedicine and as antimicrobial materials.…”
Section: Introductionmentioning
confidence: 99%